Pengaruh Penggunaan Strategi Tasmi` Terhadap Kualitas Hafalan Al-Qur`an Siswa Di MTs Madinatussalam Medan - Putra, Muhammad Yunanda Yano; Masitah, Widya (Al-Ulum: Jurnal Pendidikan Islam, 2024)
The aim of this research is to determine the quality of students' memorization of the Al-Quran and the influence of the tasmi` method on the quality of memorization. The method used in this research is a quantitative experimental method with pretest and posttest types with a sample of 35 students. The data measuring tools used are observation, tests and documentation. The results of this research were analyzed using statistical data analysis with the SPSS application. The results of the research show that the average value of the experimental class is that the class using the Tasmi method is higher than before using the Tasmi` method. As well as memorization fluency, letter fluency, waqf signs, recitation and memory for rote reading. Thus it can be concluded that there is a difference in the quality of students' memorization of the Al-Qur'an on the topic of the Al-Qur'an between before using the tasmi` method and after using the tasmi` method on the quality of students' memorization of the Al-Qur'an in tahfiz subjects at MTs Madinatussalam.